2017
DOI: 10.1515/intag-2016-0044
|View full text |Cite
|
Sign up to set email alerts
|

Influence of wood-derived biochar on the compactibility and strength of silt loam soil

Abstract: A b s t r a c t. Biochar is proven to enhance soil fertility and increase crop productivity. Given that the influence of biochar on soil compaction remains unclear, selected physico-mechanical properties of soil amended with wood-derived biochar were assessed. For unamended silt loam, the bulk density, maximum bulk density, optimum moisture content, plastic limit, liquid limit, and plasticity index were 1.05 Mg m -3 , 1.69 Mg m -3 , 16.55, 17.1, 29.3, and 12.2%, respectively. The penetration resistance and she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 35 publications
0
4
1
Order By: Relevance
“…In our study, the soil was not excessively compacted with PR values below 2 MPa, which has been observed as a critical limit for root growth in a variety of soils [55]. Previous studies such as Reference [56] and Reference [20] have observed reductions of up to 66% in PR with biochar additions, but these were both in repacked soil cores at a lab scale and where two to 10 times more biochar was applied when compared to our study. These amounts may be unrealistic and uneconomic for farmers to apply.…”
Section: Biochar Effects On Soil Physical Propertiescontrasting
confidence: 46%
See 1 more Smart Citation
“…In our study, the soil was not excessively compacted with PR values below 2 MPa, which has been observed as a critical limit for root growth in a variety of soils [55]. Previous studies such as Reference [56] and Reference [20] have observed reductions of up to 66% in PR with biochar additions, but these were both in repacked soil cores at a lab scale and where two to 10 times more biochar was applied when compared to our study. These amounts may be unrealistic and uneconomic for farmers to apply.…”
Section: Biochar Effects On Soil Physical Propertiescontrasting
confidence: 46%
“…Once again, the mechanisms involved rely upon interactions between biochar and soil properties. In clay soils, biochar has been shown to reduce soil tensile strength and the plasticity index (degree of swelling/shrinkage), but usually requires large application rates [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Bora et al 22 reported an unaltered or decreased UCS value of silty sand due to increased biochar content. Ahmed et al 30 observed a decrease in shear strength on silty loam soil attributed to the biochar addition. Sadasivam and Reddy 15 and Xu et al 31 reported an increase in shear strength parameters owing to biochar application on silty clay and purely clay soil.…”
Section: Introductionmentioning
confidence: 99%
“…Fiber reinforcement serves as a novel method for soil stabilization, aimed at enhancing geotechnical properties through the uniform integration of various fiber types, including wood, polypropylene, polyester, and polyethylene [7][8][9][10]. This technique notably improves the soil's shear, tensile, and compressive strengths, as well as its load-bearing capacity.…”
Section: Introductionmentioning
confidence: 99%